Current research status and hotspots of precancerous lesions of gastric cancer: a bibliometric analysis - Huang, Yan; Wang, Dexin; Liu, Yuzhuo; Xu, Xiaonan; Chen, Li; Ma, Zhuolin; Liu, Zhaoxia (Frontiers in Oncology, 2025)
BackgroundGastric cancer is the fifth most common cancer worldwide, and its lack of specific symptoms presents a significant challenge for early diagnosis. Therefore, the identification and detection of precancerous lesions of gastric cancer (PLGC) are essential for its prevention. We performed a comprehensive bibliometric analysis to explore the research trends and emerging topics in this field, aiming to deepen our understanding of PLGC.ObjectiveThis study utilizes a bibliometric approach with network analysis to explore the progress and trends in PLGC research. The findings aim to provide a foundation and guidance for further in-depth investigations into PLGC.MethodsThis study used VOSviewer and CiteSpace software to collect relevant literature on PLGC from the Web of Science Core Collection, covering the period from 2005 to 2024. Data visualization analysis was performed on the number of publications, countries, institutions, journals, authors, keywords, and citation counts of these articles.ResultsA total of 1,141 relevant articles were included in the analysis. The results showed a year-on-year increase in the number of publications from 2005 to 2024. The country, institution, author, and journal with the highest publication output in this field were China, Peking University, Wei-Cheng You, and World Journal of Gastroenterology, respectively. The most frequently occurring keywords in the PLGC field were “Helicobacter pylori,” “intestinal metaplasia,” “risk,” “infection,” and “atrophic gastritis.” Additionally, “chronic atrophic gastritis” and “inflammation” have emerged as hot topics for future research.ConclusionThis bibliometric analysis highlights the hot topics and emerging trends in PLGC research, aiming to provide valuable guidance for future studies. Our findings indicate that mechanistic studies and clinical diagnosis will be key areas of focus in upcoming research.